2015
DOI: 10.17987/icfj.v1i3.34
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Myocardial Viability: A Review of Current Non Invasive Imaging Techniques

Abstract: Coronary artery disease (CAD) is the most prevalent and<br />single most common cause of morbidity and mortality1 with<br />the resulting left ventricular dysfunction (LVD) an important<br />complication2. Worldwide, CAD accounts for 5.7 million new<br />cases per year, of these 1.3 million in Europe alone3. In addition,<br />it imposes a substantial share of health service resources and<br />expenses, an impaired quality of life, disability and high social<br />cost3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this regard, future studies aimed at comparing the prognostic value of different models for the estimation of mFS and ScmFS may be of clinical interest. Moreover, the potential application of LV circ midwall indexes to viability studies is worthy of exploration [58]. Previous studies suggested that changes in LV circ midwall function during low-dose dobutamine are independent determinants of LV stroke index reserve [59], and may predict functional recovery after myocardial infarction [60].…”
Section: Clinical Implications and Study Limitationsmentioning
confidence: 99%
“…In this regard, future studies aimed at comparing the prognostic value of different models for the estimation of mFS and ScmFS may be of clinical interest. Moreover, the potential application of LV circ midwall indexes to viability studies is worthy of exploration [58]. Previous studies suggested that changes in LV circ midwall function during low-dose dobutamine are independent determinants of LV stroke index reserve [59], and may predict functional recovery after myocardial infarction [60].…”
Section: Clinical Implications and Study Limitationsmentioning
confidence: 99%
“…Several non-invasive imaging modalities are used to assess myocardial viability and to identify markers of functional recovery. These imaging modalities have different diagnostic accuracy and limitations [9] . Assessment of systolic function and contractile reserve within areas of dysfunction are based on the imaging of dysfunctional myocardium using dobutamine stress echocardiography, Doppler tissue imaging and dobutamine stress cardiac magnetic resonance (CMR).…”
Section: Imaging Techniques Employed For Viability Assessmentmentioning
confidence: 99%
“…6,7 In the section on CMR, we are updated of the added value of late gadolinium enhancement patterns, which provide diagnostic utility for distinguishing between ischaemic and non-ischaemic cardiomyopathy, 8 and to predict viability and recovery of contractile function after revascularisation. 9,10 There is also a valuable update on the growing role of multi-detector CT, as well as hybrid imaging techniques that combine the advantages of multiple modalities. Heart Failure) study.…”
mentioning
confidence: 99%